(untitled) - Poe, Edgar Allan; Edgar Allan Poe; retold by Margaret Naudi (Oxford,New York, 2000)
The human mind is a dark, bottomless pit, and sometimes it works in strange and frightening ways. That sound in the night ...is it a door banging in the wind, or a murdered man knocking inside his coffin? The face in the mirror ...is it yours, or the face of someone standing behind you, who is never there when you turn round? These famous short stories by Edgar Allan Poe, that master of horror, explore the dark world of the imagination, where the dead live and speak, where fear lies in every shadow of the mind
Keywords: Readers (Adult); English language